Um Sesc no Porto - Walter Afonso Rigueti (2020)
This dissertation is intended as an essay on the relationship between architecture and free time for personal development, whether physical or intellectual, and its contributions to society. The collection of theoretical principles on the understanding of free time and leisure collaborated for the subsequent project exercise of a Sesc unit implanted in the city of Porto. The research carried out on the history of the institution in question, added to the analysis of two reference units, was fundamental for a better understanding of how Sesc operates and what its objectives are for the society in which it is inserted. The proposal of the Porto unit was made with the intention of bringing to the city a socio-cultural equipment that offers activities directed to the well being and development of the Porto society.